1979
DOI: 10.1126/science.451538
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Extra-Renal 1 α-Hydroxylation of 25-Hydroxyvitamin D 3 in Pregnancy

Abstract: The kidneys are thought to be the only organs capable of 1 alpha-hydroxylation of vitamin D and its metabolites. We have examined the in vivo conversion of 3H-(25,26)-25-hydroxyvitamin D3(25OHD3) to 3H-(25,26)-1 alpha,25-dihydroxyvitamin D3 [1 alpha,25(OH)2D3] in vitamin D-deficient, pregnant and nonpregnant rats. As expected, nephrectomy of nonpregnant, vitamin D-deficient rats prevented the conversion of 25OHD3 to 1 alpha,25(OH)2D3. In contrast, nephrectomy of pregnant, vitamin D-deficient rats reduced but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
3

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(96 citation statements)
references
References 15 publications
2
91
0
3
Order By: Relevance
“…More than 30 y ago, the placenta was identified as a major site for conversion of 25OHD to the active form of vitamin D, 1,25-dihydroxyvitamin D 3 (1,25[OH] 2 D 3 ), with both maternal decidua and fetal trophoblast demonstrating activity of the enzyme 1a-hydroxylase (CYP27B1) (7,8). However, since then, the precise function of this extrarenal CYP27B1 has remained unclear.…”
mentioning
confidence: 99%
“…More than 30 y ago, the placenta was identified as a major site for conversion of 25OHD to the active form of vitamin D, 1,25-dihydroxyvitamin D 3 (1,25[OH] 2 D 3 ), with both maternal decidua and fetal trophoblast demonstrating activity of the enzyme 1a-hydroxylase (CYP27B1) (7,8). However, since then, the precise function of this extrarenal CYP27B1 has remained unclear.…”
mentioning
confidence: 99%
“…4). Following the reports of Weisman et al [5], Gray et al [6], and Tanaka et al [7], kidney is no longer considered to be the sole site of 25-(OH)D,-1 a-hydroxylation during pregnancy. Several studies have reported that the term human feto-placental unit can produce 1,25-(OH),D, [8-131.…”
Section: Resultsmentioning
confidence: 99%
“…This concept is based on experimental results showing that 1,25-(OH)*D3 is no longer formed after bilateral nephrectomy [l]. However, this is clearly not the case during pregnancy, as rat maternal blood contains 1,25-(OH),D, even after experimental bilateral nephrectomy [5,6], and as foeto-placental tissues from both animals and humans synthesize 1,25-(OH),D, in vitro [7-131. Studies on the ability of the human uterine cells to synthesize 1,25-(OH),D, have so far been mostly limited to the late pregnancy period [g-13], and/or have involved incubations with whole tissue homogenates [8,9,12,13]. The location and characterization of the cells responsible for the 1,25-(OH),D, synthesis in the feto-placental unit at this time of pregnancy remains a fertile field for debate [8-131.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the placenta was one of the first of these extra-renal tissues shown to be capable of synthesizing 1,25(OH) 2 D, with CYP27B1 activity being detectable in both maternal decidua and fetal trophoblast. 26,27 Since then we have characterized the spatio-temporal organization of placental CYP27B1 and VDR across gestation, confirming that the enzyme and receptor are localized to both the maternal decidua and fetal trophoblast. Significantly, both proteins are more abundant in 1 st and 2 nd trimester tissue.…”
Section: Vitamin D and Human Pregnancy 69mentioning
confidence: 95%